Effect of cadmium and zinc contamination on the population dynamics of soil microorgani - Kovács, Zsuzsa (Acta Agraria Debreceniensis, 2014)
Changes in the population dynamics of microorganisms in a soil artificially contaminated with various doses of cadmium and zinc was examined from a quantitative point of view, under laboratory circumstances. The research was based on a chernozem soil originating from the area of a long-term microelement contamination model experiment (Nagyhörcsökpuszta, Hungary), which was carried out during 1991 in the Experimental Site of the Institute of Soil Science and Agricultural Chemistry, Centre for Agricultural Researche Hungarian Academy of Sciences, Budapest, Hungary. According to the amount of bacteria, microscopic fungi and nitrifying bacteria, it can be stated that the effect of contamination can be observed even in the perspective of nearly two decades. In more cases significant changes in the number of soil bacteria and microscopic fungi could be observed, and the nitrification activity increased in case of both microelements. Therefore the further research of changes in microbial activity of these soils can provide novel scientific results.